'Swa'-jal-dhara or 'Pay'-jal-dhara-Sector Reform and the Right to Drinking Water in Rajasthan and Maharashtra - Preeti Sampat (Law, Environment and Development Journal, 2007)
Since the ascent of economic liberalisation in the 1990s, Washington Consensus policies - exemplified by structural adjustment and reform - have become the norm across the globe. As a result the State redefines its role from that of a provider of basic services to a 'facilitator' that enables access to these services. Resources like water, energy, health and education are now called socio-economic goods that people must own and maintain on their own. Increasingly in all service sectors - energy, health, education or water-'demand-driven' projects formulated and executed by 'user committees' that are supposed to establish 'community ownership' through initial cost-sharing with all operations and maintenance costs borne by the users. Added to this, establishment of independent regulatory commissions, like those witnessed in the power sector, mean that citizens can no longer hold the State accountable for securing basic services for citizens.